Community-Led Regeneration A Toolkit for Residents and Planners - Sendra, Pablo (UCL Press, 2020)
Through seven London case studies of communities opposing social housing demolition and/or proposing community-led plans, Community-Led Regeneration offers a toolkit of planning mechanisms and other strategies that residents and planners working with communities can use to resist demolition and propose community-led schemes. The case studies are Walterton and Elgins Community Homes, West Ken and Gibbs Green Community Homes, Cressingham Gardens Community, Greater Carpenters Neighbourhood Forum, Focus E15, People's Empowerment Alliance for Custom House (PEACH), and Alexandra and Ainsworth Estates. Together, these case studies represent a broad overview of groups that formed as a reaction to proposed demolitions of residents' housing, and groups that formed as a way to manage residents' homes and public space better.